Respite care and short breaks for young adults aged 18-40 with complex health-care needs: mixed-methods systematic review and conceptual framework development - Katherine Knighting; Gerlinde Pilkington; Jane Noyes; Brenda Roe; Michelle Maden; Lucy Bray; Barbara Jack; Mary O'Brien; Julia Downing; Céu Mateus; Sally Spencer (National Institute for Health Research, 2021)
Background: The number of young adults with complex health-care needs due to life-limiting conditions/complex physical disability has risen significantly over the last 15 years, as more children now survive into adulthood. The transition from children to adult services may disrupt provision of essential respite/short break care for this vulnerable population, but the impact on young adults, families and providers is unclear. Aim: To review the evidence on respite care provision for young adults (aged 18-40 years) with complex health-care needs, provide an evidence gap analysis and develop a conceptual framework for respite care. Design: A two-stage mixed-methods systematic review, including a knowledge map of respite care and an evidence review of policy, effectiveness, cost-effectiveness and experience. Data sources: Electronic databases and grey/unpublished literature were searched from 2002 to September 2019. The databases searched included Cumulative Index to Nursing and Allied Health Literature, MEDLINE, EMBASE, PsycINFO, Applied Social Sciences Index and Abstracts, Health Management Information Consortium, PROSPERO, Turning Research into Practice, COnNECT+, British Nursing Index, Web of Science, Social Care Online, the National Institute for Health Research Journals Library, Cochrane Effective Practice and Organisation of Care specialist register, databases on The Cochrane Library and international clinical trials registers. Additional sources were searched using the CLUSTER (Citations, Lead authors, Unpublished materials, Scholar search, Theories, Early examples, Related projects) approach and an international 'call for evidence'. Methods and analysis: Multiple independent reviewers used the SPICE (Setting, Perspective, Intervention/phenomenon of interest, Comparison, Evaluation) framework to select and extract evidence for each stage, verified by a third reviewer. Study/source characteristics and outcomes were extracted. Study quality was assessed using relevant tools. Qualitative evidence was synthesised using a framework approach and UK policy was synthesised using documentary content analysis. GRADE-CERQual (Grading of Recommendations Assessment, Development and Evaluation-Confidence in the Evidence from Reviews of Qualitative Research) was used to assess confidence in the evidence. Logic models developed for each type of respite care constituted the conceptual framework. Results: We identified 69 sources (78 records) from 126,267 records. The knowledge map comprised the following types of respite care: residential, home based, day care, community, leisure/social provision, funded holidays and emergency. Seven policy intentions included early transition planning and prioritising respite care according to need. No evidence was found on effectiveness and cost-effectiveness. Qualitative evidence focused largely on residential respite care. Facilitators of accessible/acceptable services included trusted and valued relationships, independence and empowerment of young adults, peer social interaction, developmental/age-appropriate services and high standards of care. Barriers included transition to adult services, paperwork, referral/provision delay and travelling distance. Young adults from black, Asian and minority ethnic populations were under-represented. Poor transition, such as loss of or inappropriate services, was contrary to statutory expectations. Potential harms included stress and anxiety related to safe care, frustration and distress arising from unmet needs, parental exhaustion, and a lack of opportunities to socialise and develop independence. Limitations: No quantitative or mixed-methods evidence was found on effectiveness or cost-effectiveness of respite care. There was limited evidence on planned and emergency respite care except residential. Conclusions: Policy intentions are more comprehensively met for young people aged < 18 years who are accessing children's services. Young adults with complex needs often 'fall off a cliff' following service withdrawal and this imbalance needs addressing. Future work: Research to quantify the effectiveness and cost-effectiveness of respite care to support service development and commissioning. Development of a core set of outcomes measures to support future collation of evidence. Study registration: This study is registered as PROSPERO CRD42018088780. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 9, No. 6. See the NIHR Journals Library website for further project information.